Metabolic reprogramming by PCK1 promotes TCA cataplerosis, oxidative stress and apoptosis in liver cancer cells and suppresses hepatocellular carcinoma - Liu, Meng-Xi; Jin, Lei; Sun, Si-Jia; Liu, Peng; Feng, Xu; Cheng, Zhou-Li; Liu, Wei-Ren; Guan, Kun-Liang; Shi, Ying-Hong; Yuan, Hai-Xin; Xiong, Yue (Oncogene, 2018)
Phosphoenolpyruvate carboxykinase (PEPCK or PCK) catalyzes the first rate-limiting step in hepatic gluconeogenesis pathway to maintain blood glucose levels. Mammalian cells express two PCK genes, encoding for a cytoplasmic (PCPEK-C or PCK1) and a mitochondrial (PEPCK-M or PCK2) isoforms, respectively. Increased expressions of both PCK genes are found in cancer of several organs, including colon, lung, and skin, and linked to increased anabolic metabolism and cell proliferation. Here, we report that the expressions of both PCK1 and PCK2 genes are downregulated in primary hepatocellular carcinoma (HCC) and low PCK expression was associated with poor prognosis in patients with HCC. Forced expression of either PCK1 or PCK2 in liver cancer cell lines results in severe apoptosis under the condition of glucose deprivation and suppressed liver tumorigenesis in mice. Mechanistically, we show that the pro-apoptotic effect of PCK1 requires its catalytic activity. We demonstrate that forced PCK1 expression in glucose-starved liver cancer cells induced TCA cataplerosis, leading to energy crisis and oxidative stress. Replenishing TCA intermediate α-ketoglutarate or inhibition of reactive oxygen species production blocked the cell death caused by PCK expression. Taken together, our data reveal that PCK1 is detrimental to malignant hepatocytes and suggest activating PCK1 expression as a potential treatment strategy for patients with HCC.